Analisis Kepuasan Nasabah Dalam Pelayanan Produk dan Jasa di BSI KCP Tuban - Faiqoh Isti Anah, Elok; Puspita Sari, Yuyun (Jurnal Perbankan Syariah, 2024)
Finding out how satisfied BSI KCP Tuban customers are is the aim of this study. This study is quantitative in nature and uses closed questionnaires to get data from samples of thirty-one participants. We used SPSS software version 16 to conduct validity tests, F tests, and reliability testing. The study's findings indicate that customer satisfaction is influenced by the goods and services provided by BSI KCP Tuban. The study's findings indicate that the customer satisfaction variable is positively and significantly influenced by five markers of service satisfaction: physical proof, dependability, responsiveness, assurance, and empathy.